Impact of cooperative learning and information technology on an English language class - Lek, Kak Cheng. (2008)
A few decades ago Cooperative Learning (CL) has emerged as one of the alternatives to the traditional style of teaching. The implementation of the Information Technology Masterplan in Education has also presented teachers in Singapore with the challenge of integrating Information Technology (IT) into their everyday teaching. A case study is presented of a class of Secondary Three Normal Academic students (i.e. students who are of average academic ability) at a government school describing how Cooperative Learning and Information Technology can be integrated into the teaching of the English Language subject to enhance student learning. In particular the experiences of utilizing two multimedia CD-ROMs (Hollywood High and Famous Five) are outlined. In Hollywood High, students learnt the elements of screenwriting and story telling, including setting, plot, narration, characterization, dialogue, stage direction and sound. Students were assigned their group members and they were instructed to make the choices collaboratively, produce the screenplay and then present it to the class.